Alveolitis: Risk factors - Anampa Paucar, Marian Antonia (2022)
Alveolitis is a painful complication that occurs in the postoperative period and can be caused by different reasons. The objective of the present work was to determine the predisposing factors for the appearance of alveolitis, which shows symptoms on the second or third postoperative day. Sex, age, area of extraction, infectious processes with the presence of anaerobic microorganisms, pericoronitis, among others, are some of the risk factors. Oral contraceptives, by affecting the clotting process and producing clot lysis, are also considered as predisposing factors, as well as local anesthetic, surgical trauma, professional experience, saliva and smoking. Considered smoking as one of the factors with greater predisposition because along with nicotine cause the delay of wound healing. To collect the information, an automated search was carried out in the PubMed, SciELO and Elsevier databases. Through the analysis of scientific articles, the associated factors that give rise to dental alveolitis were recognized, this will help us to carry out guided actions for the elimination and prevention of the causal factors and thus reduce the incidence of this infectious process.